Human resource strategies for international growth - Hendry, Chris. (Routledge, 1994)
Internationalization and the domestic firm. Going international. The role of alliances in internationalization. Human resource management in the international firm. Internationalization and the Single European Market. The single European Market and the HRM response. Concluding comments: HRM and the 1990s.